2012
DOI: 10.1016/j.genhosppsych.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diabetes fatalism on medication adherence and self-care behaviors in adults with diabetes

Abstract: Objective Diabetes fatalism is defined as “a complex psychological cycle characterized by perceptions of despair, hopelessness, and powerlessness” and associated with poor glycemic control. This study examined the association between diabetes fatalism and medication adherence and self-care behaviors in adults with diabetes. Methods Data on 378 subjects with type 2 diabetes recruited from two primary care clinics in the Southeastern United States were examined. Previously validated scales were used to measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 24 publications
7
90
4
Order By: Relevance
“…Walker et al showed that patients' fatalism was significantly correlated with medication adherence (r = 0.24), diet (r = -0.26), exercise (r = -0.20), and blood sugar testing (r = -0.19) (13). In Zamanzadeh et al study, participants thought their power was from God and by believing in God and getting closer to him they increased their power to deal with the disease and the fear of death (14).…”
Section: Discussionmentioning
confidence: 99%
“…Walker et al showed that patients' fatalism was significantly correlated with medication adherence (r = 0.24), diet (r = -0.26), exercise (r = -0.20), and blood sugar testing (r = -0.19) (13). In Zamanzadeh et al study, participants thought their power was from God and by believing in God and getting closer to him they increased their power to deal with the disease and the fear of death (14).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that patients with diabetes mellitus (DM) are at high risk of decreased psychological wellbeing [1][2][3][4][5][6] which is already presence in about half of the patients at the time of diagnosis [7] . This is due to strained coping with changed life routine (such as relationships, work-related and financial issues) [6] right from the time of diagnosis of DM [7] .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to strained coping with changed life routine (such as relationships, work-related and financial issues) [6] right from the time of diagnosis of DM [7] . An international survey, the Diabetes Attitudes, Wishes and Needs second study (DAWN2), included over 16000 individuals (comprising patients, family members and healthcare providers) in 17 countries across four continents, reported that the proportion of the people with DM who were likely to have depression and diabetes-related distress (DRD) was 13.8% and 44.6%, respectively, with overall poor quality of life at 12.2% [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who use negative coping strategies perceive diabetes will negatively impact their future and are not motivated to manage the disease (Walker et al, 2012).…”
Section: Psychological Aspects Of Diabetes Managementmentioning
confidence: 99%